Nonadherence to antiepileptic drugs in Germany: A retrospective, population-based study - Gollwitzer, Stephanie; Kostev, Karel; Hagge, Mareike; Lang, Johannes; Graf, Wolfgang; Hamer, Hajo (Neurology, 2016)
To assess the effect of patient and drug characteristics on medication adherence in people with epilepsy (PWE) in a large cohort representative of the German population.Information was obtained from the Disease Analyzer database that collects anonymous demographic and medical data from practice computer systems throughout Germany. From 2010 to 2013, adult PWE were retrospectively analyzed regarding demographic characteristics, comorbidities, and treatment with antiepileptic drugs (AED). Adherence was measured using the medication possession ratio (MPR). Individuals with an MPR <80% were classified as nonadherent. Multivariate regression models were applied to assess the association of different factors with adherence by calculating adjusted odds ratios (OR) with 95% confidence intervals.A total of 31,317 PWE were included. The mean MPR was 81.1% (SD 25.7%) with 64.7% of patients showing good adherence (MPR >80%). Patient-related factors associated with good adherence to AED treatment were West German residence (OR 1.23, p < 0.0001) and learning disability (OR 1.80, p < 0.0001). Adherence was higher in patients treated with new than old (OR 1.52, p < 0.0001) and branded than generic AED (OR 1.44, p < 0.0001). Among the most common AED, levetiracetam achieved best adherence (OR 2.85, p < 0.0001), valproate lowest. Two or more daily dosages reduced adherence (TID vs QD: OR 0.84, p = 0.005; BID vs QD: OR 0.86, p = 0.011).One third of PWE treated with AED in Germany showed poor adherence, which was related to demographic characteristics and drug properties. Administration of new, well-tolerated drugs in simple dosage regimens improved AED compliance.
EVALuna2:22472